Customary Compromise and Substantive Justice: The Dalihan Na Tolu Kinship System in Family Dispute Resolution in Padangsidimpuan City from the Perspective of Sadd al-Dharī‘ah - Adi Syahputra Sirait; Mardona Siregar; Muhammad Ridwan (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2026)
The Dalihan Na Tolu system plays a dominant role in resolving family disputes within Batak society and often generates customary compromise practices that may overlook the principle of substantive justice. This study analyzes the position and influence of the Dalihan Na Tolu kinship system in contemporary family law dispute resolution and examines its compatibility with Islamic law and positive law through the sadd al dhari’ah approach. This research adopts a qualitative method combined with a sociological approach. The qualitative approach is used to explore social realities and legal practices in society, while the sociological approach examines the interaction between customary law, Islamic law, and state law in family dispute resolution. Data were collected through interviews with customary and religious leaders, field observations, and document analysis of relevant legal materials and scholarly works. The data analysis applies the sadd al dhari’ah framework to identify potential harm in customary-based dispute resolution practices under the Dalihan Na Tolu system. The findings show that the dominance of this kinship system in family disputes creates both support and criticism because it often prioritizes familial compromise and clan harmony over the protection of women’s and children’s rights as guaranteed by Islamic law and national law. This is particularly evident in divorce and inheritance cases. Furthermore, women often face limited participation in customary deliberation due to male-dominated authority structures within the Dalihan Na Tolu system. The study proposes normative reforms, including the development of customary-based dispute resolution guidelines aligned with Islamic and national law, increased female participation in deliberative processes, and stronger involvement of religious and state institutions in mediation.